The World Needs Home Economics, But Doesn’t Recognize it… How to Unveil Home Economics - Hakeem , Rubina (Nurture, 2009)
Home economists believe that amidst today’s challenges to human wellness home economics has great potential to ameliorate the situation. Evidences albeit sporadic, are found for potential of home economics to contribute to human wellness. Experts realize the need for kind of education that home economics has been providing since more than a century. However recognition of home economics itself as the kind of education needed today is still rare. This paper reviewed the reports and evidences of relevant situations and tried to explore the actions needed for realization of potential of home economics to contribute to human wellness. It emerges that philosophical reviews indicating potential of home economics are relatively easier to find than empirical studies verifying contribution of home economics education to human wellness. Large scale trials or systematic reviews providing robust evidence for potential of home economics probably have never been conducted. Various strategies including conduction of such trials are given for unveiling home economics.